Specification Design and Performances Using Computational Fluid Dynamics for Mini-Remotely Operated Underwater Vehicle - Muhammad Sawal Baital; Fakhruddin Mangkusasmito; Mitha Asyita Rahmawaty (Ultima Computing : Jurnal Sistem Komputer, 2022)
Remotely Operated Underwater Vehicle (ROV) is a submersible robotic system, used to examine various underwater characteristics and controlled by operators from shore. The applications of ROV are widely diverse, especially for exploration and marine industry. This research is to investigate pressure and drag on underwater vehicles using the CFD approach. A low-cost mini ROV with a 300 mm length was used for the research and to determine the hardware and material type required for prototype production by observing pressure and drag from the CFD simulation result. Simulation is solved using CFD software with RANSE method and Shear Stress Transport based k- ɷ was used as turbulence setting. The result indicated that to pull the mini ROV from the surface to a depth of 50 m requires a thrust of 3,9 kg and the mini ROV receiving the pressure of 7,7 bar.